New wound management of driveline infections with cold atmospheric plasma - Kremer, Jamila; Meinert, Étienne Fasolt Richard Corvin; Farag, Mina; Mueller, Florian; Soethoff, Jasmin; Karck, Matthias; Schmack, Bastian; Meyer, Anna L.; Warnecke, Gregor (Journal of cardiovascular development and disease, 2022)
The use of ventricular assist devices as a bridge to transplant or as destination therapy has increased. Wound complications increase morbidity in this cohort. Cold atmospheric plasma is a source of reactive oxygen and nitrogen species and can reduce the microbial load in skin wounds without negative effects on the surrounding tissue. We evaluated our cold atmospheric plasma treatment for LVAD driveline infections in a retrospective single-center study for peri- and postintervention outcome analysis. Between April 2019 and September 2019, 15 male patients were included (5 HVAD, 10 HeartMate III). The wounds were treated for a mean of 368.5 s with a reduction of bacterial load in treated wounds in 60% of patients, regardless of the pathogen. The most common pathogen was staphylococcus aureus (n = 8 patients). There was a significant reduction of the wound scale (scale 2.80 vs. 1.18; p < 0.001) plus a significant reduction in size (16.08 vs. 1.90 cm3; p = 0.047). Seven patients (46.6%) were free from any signs of local or systemic infection during 1-year follow-up. Five patients (33%) received a heart transplantation. Cold atmospheric plasma treatment is a potent, safe, and painless adjuvant technique for treating driveline infection without the need for repeating surgical interventions.